2011
DOI: 10.1007/s10195-011-0170-y
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hip dysplasia treated by total hip arthroplasty using cementless tapered stem in patients younger than 50 years old: results after 12-years follow-up

Abstract: BackgroundCongenital hip dysplasia may lead to severe acetabular and femoral abnormalities that can make total hip arthroplasty a challenging procedure. We assessed a series of patients affected by developmental hip dysplasia treated with total hip arthroplasty using cementless tapered stem and here we report the outcomes at long-term follow-up.Materials and methodsTwenty-eight patients (24 women and 4 men) aged between 44 and 50 years (mean 47 years) were observed. Clinical evaluation was rated with the Harri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 41 publications
4
46
0
2
Order By: Relevance
“…The patients in this study should comparable improvement in their hip scores compared to previous reports of patients who underwent complex, primary, cementless, total hip arthroplasty with conical prostheses as well as modular prostheses [1,2,6,8,11,15,19,27,28,30,31]. Despite predictable success with similar stems, it remains critically important to systematically report clinical and radiographic results whenever new technology is introduced.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The patients in this study should comparable improvement in their hip scores compared to previous reports of patients who underwent complex, primary, cementless, total hip arthroplasty with conical prostheses as well as modular prostheses [1,2,6,8,11,15,19,27,28,30,31]. Despite predictable success with similar stems, it remains critically important to systematically report clinical and radiographic results whenever new technology is introduced.…”
Section: Discussionmentioning
confidence: 87%
“…Like the former two types of stems, these taper stems can also achieve satisfactory long-term results with an incidence of thigh pain as low as 2% to 4% [4,12]. The taper cone prosthesis has a narrow round proximal cross-section that facilitates adjustment of the anteversion angle; this implant design is ideal for the femur with proximal femoral deformity such as developmental dysplasia of the hip (DDH) [1,8,15,27,28,31].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these results might not be applicable to all practices. For example, Faldini et al [4] reported on a series of 46 patients who underwent primary THA secondary to DDH using a Wagner uncemented stem aimed at achieving 10°to 20°of anteversion. However, they did not report on how many patients achieved that alignment.…”
Section: Discussionmentioning
confidence: 99%
“…The medullary canal can be small and abnormally shaped with a smaller mediolateral diameter than AP diameter [8,12]. Because of these associated anatomic variants, some authors recommend the use of modular or specially designed components to accommodate the shape of the dysplastic femur, whereas other authors have published good long-term results with cementless tapered stems [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…These abnormalities include both femur and acetabulum, which increase the complication rates and reduce long-term survival of the prosthesis. [10,11] Placing the acetabular component at a normal anatomical level has several advantages in terms of stability and biomechanics. True acetabulum has adequate bone stock at anterior and posterior columns.…”
Section: Discussionmentioning
confidence: 99%